Protective Effect of Prosopis cineraria Against N-Nitrosodiethylamine Induced Liver Tumor by Modulating Membrane Bound Enzymes and Glycoproteins - Naina Mohamed Pakkir Maideen; Ravichandiran Velayutham; Gobinath Manavalan (Tabriz University of Medical Sciences, 2012)
Purpose: The objective of the present study was to evaluate the protective effect of methanol extract of Prosopis cineraria (MPC) against N-nitrosodiethylamine (DEN, 200mg/kg) induced Phenobarbital promoted experimental liver tumors in male Wistar rats. Methods: The rats were divided into four groups, each group consisting of six animals. Group 1 served as control animals. Liver tumor was induced in group 2, 3, and 4 and Group 3 animals received MPC 200mg/kg and Group 4 animals received MPC 400mg/kg. Results: Administration of DEN has brought down the levels of membrane bound enzymes like Na+/ K+ ATPase, Mg2+ ATPase and Ca2+ATPase which were later found to be increased by the administration of Prosopis cineraria (200 and 400mg/kg) in dose dependent manner. The MPC extract also suppressed the levels of glycoproteins like Hexose, Hexosamine and Sialic acid when compared to liver tumor bearing animals. Conclusions: Our study suggests that MPC may extend its protective role by modulating the levels of membrane bound enzymes and suppressing glycoprotein levels.